Chelidonic acid evokes antidepressant-like effect through the up-regulation of BDNF in forced swimming test. Issue 14 (August 2016) - Jeong, Hyun-Ja; Yang, Shi-Young; Kim, Hee-Yun; Kim, Na-Rae; Jang, Jae-Bum; Kim, Hyung-Min
Depression is usually accompanied by neuro-inflammatory reactions. Chelidonic acid, in particular, has shown anti-inflammatory effects. The objective of this study was to evaluate the anti-depressant effects of chelidonic acid and to discuss the potential mechanisms of a forced swimming test. Chelidonic acid was administered orally once a day for 14 days. On the 14th day, chelidonic acid resulted in a significant decrease in immobility time during the forced swimming test without alteration of locomotor activity, in an open field test. Chelidonic acid also increased the number of nissl bodies in the hippocampus. Brain-derived neurotrophic factor expression and extracellular signal-regulated protein kinase phosphorylation in the hippocampus were up-regulated by the administration of chelidonic acid. Chelidonic acid administration significantly increased the mRNA expression of hippocampal estrogen receptor-β. The levels of hippocampal interleukin (IL)-1β, IL-6, and tumor necrosis factor-α were effectively attenuated by the administration of chelidonic acid. In addition, chelidonic acid significantly increased the levels of 5-hydroxytryptamine (serotonin), dopamine, and norepinephrine compared with those levels for the mice that were administered distilled water in the hippocampus. These results suggest that chelidonic acid might serve as a new therapeutic strategy for the regulation of depression associated with inflammation.